Properties of solution set of stochastic inclusions. (1993) - Kisielewicz Kisielewicz, Michał Michał
Abstract : The properties of the solution set of stochastic inclusions x t − x s ∈ c l L 2 ( ∫ s t F τ ( x τ ) d τ + ∫ s t G τ ( x τ ) d ω τ + ∫ s t ∫ ℝ n H τ, z ( x τ ) ν ˜ ( d τ, d z ) ) are investigated. They are equivalent to properties of fixed points sets of appropriately defined set-valued mappings.